"Popper" induced methemoglobinemia. Issue 3 (4th May 2022) - Elgendy, Fares; Del Rio-Pertuz, Gaspar; Nguyen, Dalena; Payne, Drew
Abstract: Methemoglobinemia is a blood disorder in which red blood cells contain methemoglobin, a form of hemoglobin that contains iron in its oxidized state, at levels >1%, often leading to a hypoxic state. It can be acquired or congenital and has been associated with nitrate or nitrite exposure. "Poppers" and "Rush" are slang terms given to drugs of the chemical class called amyl nitrate or isobutyl nitrite, which are typically inhaled and can be found over the counter. They are used with the intention of enhancing sexual performance due to their vasodilator effects, anal sphincter relaxation, and aphrodisia. We report a case of a man who developed methemoglobinemia secondary to "popper" abuse.